Determination of Decisions in Merger, Consolidation, and Acquisition of Firms Listed on the Indonesia Stock Exchange During the Covid 19 Pandemic - Rufaida, Dwiavita; Utomo, Rochmad Bayu (Journal of Social Research, 2023)
This research was conducted to examine and analyze the effect of firm size, leverage, dividend payout, and board of directors on merger, consolidation, and acquisition decisions proxied by Return on Investment (ROI). This research was conducted on firms listed on the Indonesia Stock Exchange (IDX) in 2020-2021. The sample used in this study was determined by purposive sampling method, and it produced 31 samples. The data analysis was being conducted by using multiple linear regression analysis method. The results of the analysis showed that leverage has a significant negative effect on merger, consolidation and acquisition decisions, and the board of directors has a significant positive effect on merger, consolidation and acquisition decisions, and firm size. Furthermore, dividend payout has no significant effect on merger, consolidation and acquisition decisions.